2019
DOI: 10.1111/eje.12445
|View full text |Cite
|
Sign up to set email alerts
|

Instruments to measure the ability to self‐reflect: A systematic review of evidence from workplace and educational settings including health care

Abstract: Introduction:Self-reflection has become recognised as a core skill in dental education, although the ability to self-reflect is valued and measured within several professions. This review appraises the evidence for instruments available to measure the self-reflective ability of adults studying or working within any setting, not just health care. Materials and Methods:A systematic review was conducted of 20 electronic databases (including Medline, ERIC, CINAHL and Business Source Complete) from 1975 to 2017, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 139 publications
(392 reference statements)
1
12
0
Order By: Relevance
“…Rubrics are used in education to decrease rater bias and increase validity and reliability of ratings when there are multiple raters used to evaluate an assignment. This research is in line with a recent systematic review looking at how to measure the ability to self‐reflect, with grading rubrics identified as one of three types of recommended assessment instruments 15 . The faculty raters commented frequently about the students’ writing style.…”
Section: Discussionsupporting
confidence: 82%
“…Rubrics are used in education to decrease rater bias and increase validity and reliability of ratings when there are multiple raters used to evaluate an assignment. This research is in line with a recent systematic review looking at how to measure the ability to self‐reflect, with grading rubrics identified as one of three types of recommended assessment instruments 15 . The faculty raters commented frequently about the students’ writing style.…”
Section: Discussionsupporting
confidence: 82%
“…PRISM was found to be superior against numeric scale regarding self-reflection in the current pilot study. A numeric scale (or scoring) as rubric tool for self-reflection has been evaluated in several studies [ 7 ]. A systematic review did not confirm a superiority of any instrument [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches are available, e.g., self-reflection combined with peer-feedback, video-watching, or expert-feedback [ 9 , 10 ]. Furthermore, a recent systematic review reported on the available instruments to measure the ability of self-reflection [ 7 ]. Thereby, rubrics (or scoring guides), self-reported scales, and observed behavior were differentiated, and it has been concluded that none of these tools can be recommended as single measure [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this merit is based on a consensus on the concept of reflection in order to subject it to solid empirical testing. From the dynamic perspective, this consensus still remains an ideal (Williams et al, 2019 )–or rather, an impossibility. To further our understanding of both positions, we juxtapose the technicist and dynamic approaches.…”
Section: Discussionmentioning
confidence: 99%